Non-aqueous electrolyte secondary battery

By adding a specific range of graphite particles and SBR components to the negative electrode active material layer of the nonaqueous electrolyte secondary battery, the problem of reducing charge and discharge cycle characteristics is solved, and the reliability of the battery is improved.

CN112292772BActive Publication Date: 2025-04-29PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN201980039730.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-06-15
Filing Date
2019-06-04
Publication Date
2025-04-29
Estimated Expiration
2039-06-04

AI Technical Summary

Technical Problem

The characteristics of existing nonaqueous electrolyte secondary batteries are easily reduced during the charge and discharge cycle, which affects the reliability of the battery.

Method used

A negative electrode having a negative electrode active material layer is used, which contains graphite particles and styrene-butadiene copolymer rubber (SBR) components, the internal void ratio of the graphite particles is 1% to 5%, the inter-particle void ratio of the negative electrode active material layer is 10% to 20%, and the content of the SBR component is 1.5% to 3% by mass.

Benefits of technology

The reduction of charge and discharge cycle characteristics is effectively suppressed and the reliability of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112292772B_ABST
    Figure CN112292772B_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide a nonaqueous electrolyte secondary battery capable of suppressing the reduction of charge and discharge cycle characteristics. As one embodiment of the present invention, the nonaqueous electrolyte secondary battery comprises a negative electrode having a negative electrode active material layer, wherein the negative electrode active material layer comprises: a negative electrode active material containing graphite particles, and at least one SBR component selected from styrene-butadiene copolymer rubber and its modified body, the internal porosity of the graphite particles is 1% to 5%, the interparticle porosity of the negative electrode active material layer is 10% to 20%, and the content of the SBR component is 1.5% to 3% by mass relative to the mass of the negative electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a nonaqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries using a carbon material as a negative electrode active material are widely used as high energy density secondary batteries.

[0003] For example, Patent Documents 1 to 3 disclose non-aqueous electrolyte secondary batteries using a graphite material having a relatively large pore volume as a carbon material.

[0004] For example, Patent Document 4 discloses a non-aqueous electrolyte secondary battery using densified carbon having an internal porosity of 5% or less as a carbon material.

[0005] For example, Patent Documents 5 and 6 disclose a nonaqueous electrolyte secondary battery using a negative electrode containing a styrene-butadiene copolymer rubber and a carbon material.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-7597

[0009] Patent Document 2: Japanese Patent Application Laid-Open No. 10-21919

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 10-236809

[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 9-320600

[0012] Patent Document 5: Japanese Patent Application Laid-Open No. 4-342966

[0013] Patent Document 6: Japanese Patent Application Laid-Open No. 11-288718 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] In order to improve the reliability of nonaqueous electrolyte secondary batteries, it is necessary to suppress the reduction in charge and discharge cycle characteristics.

[0016] Therefore, an object of the present invention is to provide a non-aqueous electrolyte secondary battery capable of suppressing a decrease in charge and discharge cycle characteristics.

[0017] Means used to solve problems

[0018] A nonaqueous electrolyte secondary battery as one embodiment of the present invention comprises a negative electrode having a negative electrode active material layer, wherein the negative electrode active material layer comprises: a negative electrode active material containing graphite particles, and at least one SBR component selected from styrene-butadiene copolymer rubber and modified bodies thereof, wherein the internal porosity of the graphite particles is 1% to 5%, the interparticle porosity of the negative electrode active material layer is 10% to 20%, and the content of the SBR component is 1.5% to 3% by mass relative to the mass of the negative electrode active material.

[0019] Effects of the Invention

[0020] According to one aspect of the present invention, it is possible to suppress a decrease in charge and discharge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment.

[0022] Figure 2 (A) is a schematic enlarged view showing a part of the cross section of the negative electrode active material layer, Figure 2 (B) means Figure 2 (A) is a schematic enlarged view of a cross section of a graphite particle in a cross section of a negative electrode active material layer. DETAILED DESCRIPTION

[0023] (Foundation that forms the basis of the present invention)

[0024] Compared with the graphite particles with high internal porosity, the graphite particles with low internal porosity are suppressed in the destruction of the graphite particles in the charge and discharge cycle and the decomposition reaction of the non-aqueous electrolyte accompanying it, so there is a tendency to suppress the reduction of the charge and discharge cycle characteristics of the non-aqueous electrolyte secondary battery. However, if only the graphite particles with low internal porosity are used, the reduction of the charge and discharge cycle characteristics of the non-aqueous electrolyte secondary battery can not be effectively suppressed sometimes. It is believed that the reason is that in the case of using graphite particles with low internal porosity, the contact amount with the non-aqueous electrolyte is easily reduced, and the particles are difficult to crush when forming an electrode, and the cohesiveness of the particles based on the bonding material is easily reduced. Therefore, the inventors and others found through in-depth research that in order to effectively suppress the reduction of the charge and discharge cycle characteristics of the non-aqueous electrolyte secondary battery, on the basis of using graphite particles with low internal porosity, it is also necessary to set the interparticle porosity of the negative electrode active material layer constituting the negative electrode to a specified range, and the content of the styrene-butadiene copolymer rubber or its modified body that functions as a bonding material is set to a specified range, so that the non-aqueous electrolyte secondary battery of the scheme shown below is thought of.

[0025] A nonaqueous electrolyte secondary battery as one embodiment of the present invention is characterized in that it has a negative electrode having a negative electrode active material layer, wherein the negative electrode active material layer comprises: a negative electrode active material containing graphite particles, and at least one SBR component selected from styrene-butadiene copolymer rubber and its modified form, the internal porosity of the graphite particles is 1% to 5%, the interparticle porosity of the negative electrode active material layer is 10% to 20%, and the content of the SBR component is 1.5% to 3% by mass relative to the mass of the negative electrode active material.

[0026] Here, it is believed that if the interparticle porosity of the negative electrode active material layer is 10% to 20% as in one embodiment of the present invention, a certain amount of non-aqueous electrolyte can be maintained in the negative electrode active material layer, so the contact amount of graphite particles with an internal porosity of 1% to 5% and the non-aqueous electrolyte can be fully ensured. In addition, it is believed that if the content of the SBR component is 1.5% to 3% by mass as in one embodiment of the present invention, sufficient adhesion between the graphite particles can be ensured. In this way, it can be considered that according to the non-aqueous electrolyte secondary battery as one embodiment of the present invention, the reduction in the contact amount of graphite particles and the non-aqueous electrolyte in the case of using graphite particles with low internal porosity, the reduction in the adhesion between the graphite particles, etc., can be suppressed, so the reduction in charge and discharge cycle characteristics can be effectively suppressed. It should be noted that if the interparticle porosity of the negative electrode active material layer exceeds 20%, the retention amount of the non-aqueous electrolyte becomes high, and on the other hand, the contact rate between the graphite particles becomes low, and it is difficult to suppress the reduction in charge and discharge cycle characteristics. If the content of the SBR component exceeds 3% by mass, the adhesion between the graphite particles increases, while the resistance of the interface between the graphite particles increases, making it difficult to suppress a decrease in the charge-discharge cycle characteristics.

[0027] Hereinafter, an example of an embodiment will be described in detail with reference to the drawings. It should be noted that the nonaqueous electrolyte secondary battery of the present invention is not limited to the embodiment described below. In addition, the drawings referred to in the description of the embodiment are schematic drawings.

[0028] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. Figure 1The non-aqueous electrolyte secondary battery 10 shown in the figure comprises a wound electrode body 14 in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween, a non-aqueous electrolyte, insulating plates 18 and 19 respectively arranged above and below the electrode body 14, and a battery case 15 for accommodating the above components. The battery case 15 is composed of a shell body 16 in a cylindrical shape with a bottom, and a sealing body 17 for sealing the opening of the shell body 16. It should be noted that other forms of electrode bodies such as a laminated electrode body in which a positive electrode and a negative electrode are alternately laminated with a separator interposed therebetween may be used instead of the wound electrode body 14. In addition, as the battery case 15, a cylindrical, square, coin-shaped, button-shaped, or other metal outer can, a bag-type outer body formed by laminating a resin sheet and a metal sheet, and the like can be exemplified.

[0029] The shell body 16 is, for example, a metal outer can in a bottomed cylindrical shape. A gasket 28 is provided between the shell body 16 and the sealing body 17 to ensure the airtightness of the inside of the battery. The shell body 16 has, for example, a bulging portion 22 in which a part of the side surface bulges inward and supports the sealing body 17. The bulging portion 22 is preferably formed in an annular shape along the circumference of the shell body 16, and supports the sealing body 17 on its upper surface.

[0030] The sealing body 17 has a structure in which a filter 23, a lower valve body 24, an insulating component 25, an upper valve body 26 and a cap 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected to each other at their respective central portions, and an insulating component 25 is present between their respective peripheral portions. If the internal pressure of the non-aqueous electrolyte secondary battery 10 rises due to heat caused by an internal short circuit, for example, the lower valve body 24 deforms and ruptures in a manner that pushes the upper valve body 26 toward the cap 27 side, and the current path between the lower valve body 24 and the upper valve body 26 is blocked. If the internal pressure rises further, the upper valve body 26 ruptures, and the gas is discharged from the opening of the cap 27.

[0031] Figure 1 In the non-aqueous electrolyte secondary battery 10 shown, the positive electrode lead 20 attached to the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 attached to the negative electrode 12 extends to the bottom side of the case body 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the bottom plate of the sealing body 17, that is, the lower surface of the filter 23, by welding or the like, and the top plate of the sealing body 17, that is, the cap 27 electrically connected to the filter 23, becomes the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the case body 16 by welding or the like, and the case body 16 becomes the negative terminal.

[0032] Hereinafter, each component of the nonaqueous electrolyte secondary battery 10 will be described in detail.

[0033] [negative electrode]

[0034] The negative electrode 12 includes a negative electrode current collector formed of, for example, metal foil, and a negative electrode active material layer formed on the current collector. The negative electrode current collector may be made of, for example, copper or other metal foil that is stable in the potential range of the negative electrode, or a film having the metal disposed on the surface.

[0035] The negative electrode active material layer includes: a negative electrode active material containing graphite particles, and an SBR component selected from at least one of styrene-butadiene copolymer rubber and its modified form. The negative electrode 12 can be made by, for example, preparing a negative electrode mixture slurry containing a negative electrode active material, an SBR component, etc., applying the negative electrode mixture slurry on a negative electrode collector and drying it to form a negative electrode active material layer, and press-forming the negative electrode active material layer.

[0036] Figure 2 (A) is a schematic enlarged view showing a part of the cross section of the negative electrode active material layer, Figure 2 (B) means Figure 2 (A) is a schematic enlarged view of a cross section of a graphite particle on a cross section of a negative electrode active material layer. Figure 2 As shown in (A), the negative electrode active material layer has gaps 32 (hereinafter referred to as inter-particle gaps 32) formed between particles such as graphite particles 30 that form the negative electrode active material layer. Figure 2 As shown in (B), in the cross-sectional view of the graphite particle 30, the graphite particle 30 has closed voids 34 (hereinafter referred to as internal voids 34) that are not connected from the inside of the particle to the particle surface, and voids 36 (hereinafter referred to as external voids 36) that are connected from the inside of the particle to the particle surface.

[0037] As described above, the interparticle porosity of the negative electrode active material layer may be 10% to 20% in terms of suppressing the reduction of the charge-discharge cycle characteristics, preferably 12% to 18%, and more preferably 14% to 16%. In addition, as described above, the internal porosity of the graphite particles 30 may be 1% to 5% in terms of suppressing the reduction of the charge-discharge cycle characteristics, preferably 3% to 5%. Here, the interparticle porosity of the negative electrode active material layer refers to a two-dimensional value obtained by the ratio of the area of ​​the interparticle voids 32 in the negative electrode active material layer to the cross-sectional area of ​​the negative electrode active material layer, and the internal porosity of the graphite particles 30 refers to a two-dimensional value obtained by the ratio of the area of ​​the internal voids 34 of the graphite particles 30 to the cross-sectional area of ​​the graphite particles 30. Then, the interparticle porosity of the negative electrode active material layer and the internal porosity of the graphite particles 30 are obtained according to the following procedure.

[0038] <Method for measuring interparticle void ratio and internal void ratio>

[0039] (1) Exposing the cross section of the negative electrode active material. For example, the following method can be used to expose the cross section: a portion of the negative electrode is cut and processed using an ion milling device (eg, IM4000 manufactured by Hitachi High-Technologies Corporation) to expose the cross section of the negative electrode active material layer.

[0040] (2) Using a scanning electron microscope, a reflected electron image of the cross section of the exposed negative electrode active material layer is taken. When obtaining the interparticle porosity of the negative electrode active material layer, the reflected electron image is taken at a magnification of 1,000 times, and when obtaining the internal porosity of the graphite particles, the reflected electron image is taken at a magnification of 3,000 to 5,000 times.

[0041] (3) The cross-sectional image obtained as described above is imported into a computer and binarized using image analysis software (e.g., ImageJ manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross-sectional image is converted to black and the voids in the particle cross-sectional image and the voids between particles are converted to white.

[0042] (4-1) In the case of obtaining the internal porosity of graphite particles, graphite particles with a particle size of 5 μm to 50 μm are selected from the binary processed image using image analysis software, and the area of ​​the cross section of the graphite particles and the area of ​​the internal voids present in the cross section of the graphite particles are calculated. Here, the area of ​​the cross section of the graphite particles refers to the area of ​​the region surrounded by the periphery of the graphite particles, that is, the total area of ​​the cross-sectional portion of the graphite particles. In addition, for voids with a width of less than 3 μm among the voids present in the cross section of the graphite particles, it is sometimes difficult to distinguish whether they are internal voids or external voids in image analysis, so voids with a width of less than 3 μm can be regarded as internal voids. Then, the internal porosity of the graphite particles is calculated from the calculated area of ​​the cross section of the graphite particles and the area of ​​the internal voids in the cross section of the graphite particles (area of ​​the internal voids in the cross section of the graphite particles × 100 / area of ​​the cross section of the graphite particles). The internal porosity of the graphite particles is set to the average value of 10 graphite particles.

[0043] (4-2) When determining the interparticle porosity of the negative electrode active material layer, the area of ​​the interparticle voids within the measurement range (50 μm × 50 μm) was calculated from the binary processed image using image analysis software. The above measurement range was set to the cross-sectional area of ​​the negative electrode active material layer (2500 μm 2 =50 μm×50 μm), and the interparticle void ratio of the negative electrode active material layer was calculated from the calculated area of ​​the interparticle voids (area of ​​the interparticle voids×100 / cross-sectional area of ​​the negative electrode active material layer).

[0044] The interparticle porosity of the negative electrode active material layer can be adjusted by, for example, the pressure when the negative electrode active material layer is press-formed. The pressure during press-forming also depends on the thickness of the negative electrode active material layer, for example, the linear pressure during press-forming of the negative electrode active material layer based on a calender roll is preferably in the range of 60 kg / cm to 500 kg / cm.

[0045] In addition, the interparticle porosity of the negative electrode active material layer can also be adjusted by, for example, the saturated tap density of the negative electrode active material. In order to easily adjust the interparticle porosity of the negative electrode active material layer to a range of 10% to 20%, the saturated tap density of the negative electrode active material is preferably 0.8 g / cm 3 ~1.2g / cm 3 It should be noted that the saturated tap density of the graphite particles 30 may be within the above range or outside the range. When outside the range, it is desirable to mix a plurality of graphite particles 30 having different saturated tap densities so that the saturated tap density of the negative electrode active material is within the above range.

[0046] The saturated tap density can be measured using a powder reduction tester (TPM-1 manufactured by Tsutsui Rikagaku Instruments Co., Ltd.) Specifically, 50 g of the sample (powder) is placed in a 150 ml glass measuring cylinder, and the powder filling density is obtained by tapping 1000 times with a stroke of 30 mm using the powder reduction tester, and this density is used as the saturated tap density.

[0047] The internal porosity of the graphite particles 30 can be adjusted, for example, during the production stage of the graphite particles.

[0048] <Internal porosity: 1% to 5%>

[0049] For example, coke (precursor) to be the main raw material is crushed into a specified size, and in a state where they are agglomerated with a binder, they are fired at a temperature of 2600°C or above to graphitize them, and then sieved to obtain graphite particles 30 of a desired size. The internal porosity of the graphite particles 30 can be adjusted by the particle size of the precursor after crushing and the particle size of the precursor in an agglomerated state. In addition, in the case of obtaining graphite particles 30 having an internal porosity of 1% to 5%, the average particle size (volume-based median particle size D50) of the crushed precursor is preferably in the range of, for example, 12μm to 20μm. In addition, in the case of reducing the internal porosity to a range of less than 5%, it is preferred to increase the particle size of the crushed precursor.

[0050] <Internal void ratio: 10% or more>

[0051] For example, the coke (precursor) which will become the main raw material is crushed into a specified size, and after agglomerating them with a binder, they are further pressed into a block state and fired at a temperature of more than 2600°C to graphitize them. The block-shaped molded body after graphitization is crushed and sieved to obtain graphite particles of the desired size. The internal porosity can be adjusted to more than 10% by the amount of volatile components added to the block-shaped molded body. In the case where a part of the binder added to the coke (precursor) volatilizes during firing, the binder can be used as a volatile component. Asphalt can be exemplified as such a binder. The amount of volatile components added is preferably set to more than 8% by mass relative to the block-shaped molded body.

[0052] The graphite particles 30 used in this embodiment may be natural graphite, artificial graphite, etc., without particular limitation. Artificial graphite is preferred in terms of easy adjustment of the internal porosity, etc. The interplanar spacing (d ) of the (002) plane of the graphite particles used in this embodiment based on the wide-angle X-ray diffraction method is 002 ) is preferably, for example, 0.3354 nm or more, more preferably 0.3357 nm or more, and preferably less than 0.340 nm, and more preferably less than 0.338 nm. In addition, the crystal size (Lc(002)) of the graphite particles used in this embodiment determined by X-ray diffraction is preferably, for example, 5 nm or more, more preferably 10 nm or more, and preferably less than 300 nm, and more preferably less than 200 nm. The plane spacing (d 002 When the crystal size (Lc(002)) and the crystal size (Lc(002)) satisfy the above ranges, the battery capacity of the non-aqueous electrolyte secondary battery tends to be larger than when the above ranges are not satisfied.

[0053] In addition to the graphite particles 30 used in the present embodiment, the negative electrode active material may also include other materials that can reversibly absorb and release lithium ions, such as metals such as silicon (Si) and tin (Sn) alloyed with lithium, or alloys and oxides containing metal elements such as Si and Sn. If the content of the above-mentioned other materials increases, the effect of suppressing the reduction of the charge and discharge cycle characteristics of the non-aqueous electrolyte secondary battery may not be fully obtained, so the content of the above-mentioned other materials relative to the mass of the negative electrode active material is preferably set to 10% by mass or less.

[0054] The SBR component containing at least one of styrene-butadiene copolymer rubber and its modified product used in the present embodiment functions as a binder for bonding the graphite particles 30 to each other. The modified product is a material obtained by modifying the styrene-butadiene copolymer rubber with a modifier having a polar group, and is not particularly limited, and examples thereof include amine modified products, fluorine modified products, carboxyl modified products, epoxy modified products, and alcohol modified products.

[0055] As described above, the content of the SBR component is 1.5 to 3% by mass, preferably 2 to 2.8% by mass, based on the mass of the negative electrode active material in order to suppress a decrease in the charge and discharge cycle characteristics of the nonaqueous electrolyte secondary battery.

[0056] The binder may contain components other than the SBR component, such as fluororesin, PAN, polyimide, acrylic resin, polyolefin, etc., and may also contain CMC or its salt, polyacrylic acid (PAA) or its salt, polyvinyl alcohol (PVA), etc.

[0057] [positive electrode]

[0058] The positive electrode 11 is composed of a positive electrode current collector such as a metal foil and a positive electrode active material layer formed on the positive electrode current collector. For the positive electrode current collector, a foil of a metal such as aluminum that is stable within the potential range of the positive electrode, a film in which the metal is arranged on the surface, etc. can be used. The positive electrode active material layer includes, for example, a positive electrode active material, a binder, a conductive material, etc.

[0059] The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry including a positive electrode active material, a binder, a conductive material, etc., on a positive electrode current collector and drying the mixture to form a positive electrode active material layer, and then pressure-forming the positive electrode active material layer.

[0060] Examples of the positive electrode active material include lithium transition metal oxides containing transition metal elements such as Co, Mn, and Ni. Lithium transition metal oxides are, for example, Li x CoO2、Li x NiO2、Li x MnO2、Li x Co y Ni 1-y O2、Li x Co y M 1-y O z , Li x Ni 1- y M y O z , Li x Mn2O4、Li x Mn 2-y M yO4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3). These can be used alone or in combination. In order to achieve a high capacity of the non-aqueous electrolyte secondary battery, the positive electrode active material preferably contains Li x NiO2、Li x Co y Ni 1-y O2、Li x Ni 1-y M y O z Lithium nickel composite oxides such as (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B, 0<x≤1.2, 0<y≤0.9, 2.0≤z≤2.3).

[0061] Examples of the conductive material include carbon black (CB), acetylene black (AB), Ketjen black, graphite and other carbon particles, etc. These may be used alone or in combination of two or more.

[0062] Examples of the binder include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide-based resins, acrylic resins, and polyolefin-based resins, etc. These may be used alone or in combination of two or more.

[0063] [Spacer]

[0064] For the spacer 13, for example, a porous sheet having ion permeability and insulation can be used. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be cited. As the material of the spacer, olefin resins such as polyethylene and polypropylene, cellulose, etc. are suitable. The spacer 13 can have a laminate of a cellulose fiber layer and a thermoplastic resin fiber layer such as an olefin resin. In addition, it can be a spacer including a polyethylene layer and a polypropylene layer and a multilayer spacer, and a spacer coated with a material such as an aramid resin, ceramics, etc. on the surface of the spacer can be used.

[0065] [Non-aqueous electrolyte]

[0066] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte is not limited to a liquid electrolyte (electrolyte), and can be a solid electrolyte using a gel-like polymer or the like. Among the non-aqueous solvents, for example, esters, ethers, nitriles such as acetonitrile, amides such as dimethylformamide, and mixed solvents of two or more of these can be used. The non-aqueous solvent can contain a halogen-substituted substance in which at least a portion of the hydrogen of these solvents is replaced by a halogen atom such as fluorine.

[0067] Examples of the esters include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate; chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, and methyl isopropyl carbonate; cyclic carboxylates such as γ-butyrolactone and γ-valerolactone; and chain carboxylates such as methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), and ethyl propionate.

[0068] Examples of the ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxane, 1,4-dioxane, 1,3,5-trioxane, furan, 2-methylfuran, 1,8-cineole, cyclic ethers such as crown ether, 1,2-dimethoxyethane, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethylethylene. Chain ethers such as 1,2-dimethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0069] As the halogen-substituted product, fluorinated cyclic carbonates such as fluoroethylene carbonate (FEC), fluorinated chain carbonates, fluorinated chain carboxylates such as fluoromethyl propionate (FMP), and the like are preferably used.

[0070] The electrolyte salt is preferably a lithium salt. Examples of lithium salts include LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiAlCl4, LiSCN, LiCF3SO3, LiCF3CO2, Li(P(C2O4)F4), LiPF 6-x (C n F 2n+1 ) x (1<x<6, n is 1 or 2), LiB 10 Cl 10, LiCl, LiBr, LiI, lithium chloroborane, lower aliphatic carboxylic acid lithium, Li2B4O7, Li(B(C2O4)F2) and other borates; LiN(SO2CF3)2, LiN(C1F 21+1 SO2)(C m F 2m+1 SO2) {l, m is an integer greater than 1} and other imide salts. Lithium can be used alone or in combination. Among these, LiPF6 is preferably used from the viewpoint of ion conductivity, electrochemical stability, etc. The concentration of the lithium salt is preferably 0.8 to 1.8 mol per 1 L of solvent.

[0071] Example

[0072] Hereinafter, the present invention will be further described by way of examples, but the present invention is not limited to these examples.

[0073] <Example 1>

[0074] [Production of positive electrode]

[0075] Cobalt carbonate, 0.1 mol% zirconium, 1 mol% magnesium, and 1 mol% aluminum were coprecipitated and subjected to thermal decomposition reaction to obtain cobalt tetroxide containing zirconium, magnesium, and aluminum. The mixture to which lithium carbonate was added was calcined at 850°C for 20 hours to obtain lithium cobalt oxide (LiCo) containing zirconium, magnesium, and aluminum. 0.979 Zr 0.001 Mg 0.01 Al 0.01 O2). It is used as the positive electrode active material.

[0076] The positive electrode active material was mixed in a manner of 95 parts by mass, carbon powder as a conductive material was 2.5 parts by mass, and polyvinylidene fluoride powder as a binder was 2.5 parts by mass, and then N-methyl-2-pyrrolidone (NMP) was added in an appropriate amount to prepare a positive electrode mixture slurry. The slurry was applied to both sides of a collector formed of aluminum foil (thickness 15 μm) by a doctor blade method, and after the coating was dried, the coating was rolled by a calendering roller to produce a positive electrode having a positive electrode active material layer formed on both sides of the positive electrode collector.

[0077] [Preparation of negative electrode active material]

[0078] The coke was crushed until the average particle size (median particle size D50) was 12 μm, and pitch was added as a binder to the crushed coke to agglomerate the coke until the average particle size (median particle size D50) was 17 μm. The agglomerate was calcined at a temperature of 2800°C and graphitized, and then sieved using a 250 mesh sieve to obtain graphite particles with an average particle size (median particle size D50) of 23 μm. This was used as a negative electrode active material.

[0079] [Production of negative electrode]

[0080] The negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) are mixed in a mass ratio of 100:1.5:1.5 to prepare a negative electrode mixture slurry. The slurry is applied to both sides of a current collector formed of copper foil by a doctor blade method. After the coating film is dried, it is rolled by a calendering roller at a linear pressure of 160 kg / cm to produce a negative electrode having a negative electrode active material layer formed on both sides of the negative electrode current collector. In the produced negative electrode, the internal porosity of the graphite particles and the interparticle porosity of the negative electrode active material layer are measured, and the results are 3% and 15%, respectively. The measurement method is omitted as described above.

[0081] [Preparation of non-aqueous electrolyte]

[0082] LiPF6 was dissolved at a concentration of 1 mol / L in a non-aqueous solvent in which ethylene carbonate (EC), methyl ethyl carbonate (MEC), and diethyl carbonate (DEC) were mixed in a volume ratio of 30:60:10. Furthermore, 2% by mass of vinylene carbonate (VC) and 1% by mass of fluorinated ethylene carbonate were dissolved relative to the total amount of the solution to serve as a non-aqueous electrolyte.

[0083] [Fabrication of non-aqueous electrolyte secondary battery]

[0084] (1) An electrode body is prepared by winding the positive electrode and the negative electrode with a separator composed of a polyethylene microporous film interposed therebetween, and then pressing the electrode body to form a flat wound electrode body.

[0085] (2) Prepare a sheet-shaped laminated material having a five-layer structure of polypropylene resin layer / adhesive layer / aluminum alloy layer / adhesive layer / polypropylene resin layer. Bend the laminated material to form a bottom, thereby forming a cup-shaped electrode body storage space. Use the laminated material as the battery outer casing.

[0086] (3) In a glove box under an argon atmosphere, the electrode body and the non-aqueous electrolyte were placed in the storage space of the outer casing, and then the interior of the outer casing was depressurized to allow the non-aqueous electrolyte to be impregnated into the separator. The opening of the outer casing was sealed to produce a non-aqueous electrolyte secondary battery having a height of 62 mm, a width of 35 mm, and a thickness of 3.6 mm.

[0087] <Example 2>

[0088] In the preparation of the negative electrode, the same conditions as in Example 1 were used except that the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.0. The internal porosity of the graphite particles in the prepared negative electrode and the interparticle porosity of the negative electrode active material layer were the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the prepared negative electrode was used.

[0089] <Example 3>

[0090] In the preparation of the negative electrode, the same conditions as in Example 1 were used except that the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.5. The internal porosity of the graphite particles in the prepared negative electrode and the interparticle porosity of the negative electrode active material layer were the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the prepared negative electrode was used.

[0091] <Example 4>

[0092] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.5, and the linear pressure when the coating was rolled by the calendering roller was changed to 200 kg / cm. The same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was the same as in Example 1, and the interparticle porosity of the negative electrode active material layer was 11%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0093] <Example 5>

[0094] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.5, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm. The same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was the same as in Example 1, and the interparticle porosity of the negative electrode active material layer was 18%. A non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0095] <Example 6>

[0096] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:3.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 160 kg / cm. The same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was the same as in Example 1, and the interparticle porosity of the negative electrode active material layer was 15%. A non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0097] <Example 7>

[0098] In the preparation of the negative electrode active material, the same conditions as in Example 1 were used except that the average particle size (median particle size D50) of the crushed coke was changed to 15 μm. Furthermore, the negative electrode active material prepared as described above was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:2.5, and the negative electrode was prepared in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was prepared. The internal porosity of the graphite particles in the prepared negative electrode was 1%, and the interparticle porosity of the negative electrode active material layer was the same as in Example 1.

[0099] <Example 8>

[0100] In the preparation of the negative electrode active material, the same conditions as in Example 1 were used except that the average particle size (median particle size D50) of the crushed coke was changed to 10 μm. Furthermore, the negative electrode active material prepared as described above was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:2.5, and the negative electrode was prepared in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was prepared. The internal porosity of the graphite particles in the prepared negative electrode was 5%, and the interparticle porosity of the negative electrode active material layer was the same as in Example 1.

[0101] <Comparative Example 1>

[0102] In the preparation of the negative electrode, the negative electrode active material prepared in Example 7 was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:1.0, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 1%, and the interparticle porosity of the negative electrode active material layer was the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0103] <Comparative Example 2>

[0104] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:1.0, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode and the interparticle porosity of the negative electrode active material layer were the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0105] <Comparative Example 3>

[0106] In the preparation of the negative electrode, the negative electrode active material prepared in Example 8 was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:1.0, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 5%, and the interparticle porosity of the negative electrode active material layer was the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0107] <Comparative Example 4>

[0108] [Preparation of negative electrode active material]

[0109] The coke was pulverized until the average particle size (median particle size D50) was 5 μm, and pitch was added as a binder to the pulverized coke to agglomerate it, and then an isotropic pressure was applied to form a particle with a particle size of 1.6 g / cm 3 ~1.9g / cm 3 The block-shaped body was calcined at a temperature of 2800°C to graphitize, and then the block-shaped body was crushed and sieved using a 250-mesh sieve to obtain graphite particles with an average particle size (median particle size D50) of 23 μm. This was used as the negative electrode active material of Comparative Example 4.

[0110] In the preparation of the negative electrode, the negative electrode active material of Comparative Example 4: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:1.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 10%, and the interparticle porosity of the negative electrode active material layer was 8%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0111] <Comparative Example 5>

[0112] In the preparation of the negative electrode, the negative electrode active material prepared in Comparative Example 4 was used, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 10%, and the interparticle porosity of the negative electrode active material layer was 8%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0113] <Comparative Example 6>

[0114] In the preparation of the negative electrode, the negative electrode active material prepared in Comparative Example 4 was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:2.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 10%, and the interparticle porosity of the negative electrode active material layer was 8%. A non-aqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0115] <Comparative Example 7>

[0116] In the preparation of the negative electrode active material, the same conditions as those in Comparative Example 4 were used except that the amount of asphalt was changed. Furthermore, the negative electrode active material prepared as described above was used, and the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) was mixed in a mass ratio of 100:1.5:1.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm. In addition, the negative electrode was prepared in the same manner as in Example 1, and a non-aqueous electrolyte secondary battery was prepared. The internal porosity of the graphite particles in the prepared negative electrode was 15%, and the interparticle porosity of the negative electrode active material layer was 8%.

[0117] <Comparative Example 8>

[0118] In the preparation of the negative electrode, the negative electrode active material prepared in Comparative Example 7 was used, and the linear pressure when the coating was rolled by the calendering roller was changed to 120 kg / cm, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was 15%, and the interparticle porosity of the negative electrode active material layer was 8%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0119] <Comparative Example 9>

[0120] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 350 kg / cm. The same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was the same as in Example 1, and the interparticle porosity of the negative electrode active material layer was 8%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0121] <Comparative Example 10>

[0122] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:2.0, and the linear pressure when the coating was rolled by the calendering roller was changed to 50 kg / cm. The same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode was the same as in Example 1, and the interparticle porosity of the negative electrode active material layer was 25%. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0123] <Comparative Example 11>

[0124] In the preparation of the negative electrode, the negative electrode active material: carboxymethyl cellulose (CMC): styrene-butadiene copolymer rubber (SBR) were mixed in a mass ratio of 100:1.5:3.5, and the same conditions as in Example 1 were used. The internal porosity of the graphite particles in the prepared negative electrode and the interparticle porosity of the negative electrode active material layer were the same as in Example 1. A nonaqueous electrolyte secondary battery was prepared in the same manner as in Example 1 except that the above-prepared negative electrode was used.

[0125] [Determination of Capacity Retention Rate during Charge and Discharge Cycles]

[0126] At an ambient temperature of 25°C, the non-aqueous electrolyte secondary battery of each embodiment and each comparative example is subjected to constant current charging (current 1It=800mA, end voltage 4.2V), and then constant voltage charging (voltage 4.2V, end current 40mA). Thereafter, the battery is discharged at a current value of 800mA until the end voltage is 2.5V. This charge and discharge is regarded as one cycle, and 1000 cycles are performed. Then, the capacity retention rate of the charge and discharge cycle of the non-aqueous electrolyte secondary battery of each embodiment and each comparative example is obtained by the following formula.

[0127] Capacity retention rate = (discharge capacity at the 1000th cycle / discharge capacity at the 1st cycle) × 100

[0128] The results of the capacity retention ratios of the nonaqueous electrolyte secondary batteries of the Examples and Comparative Examples during the charge and discharge cycles are summarized in Table 1. It should be noted that a higher value of the capacity retention ratio indicates that a decrease in the charge and discharge cycle characteristics is suppressed.

[0129] [Table 1]

[0130]

[0131] As can be seen from Table 1, the nonaqueous electrolyte secondary batteries of Examples 1 to 8 all show higher values ​​of capacity retention during charge and discharge cycles than the nonaqueous electrolyte secondary batteries of Comparative Examples 1 to 11. Therefore, the nonaqueous electrolyte secondary battery in which the internal porosity of the graphite particles contained in the negative electrode active material layer is 1 to 5%, the interparticle porosity of the negative electrode active material layer is 10% to 20%, and the content of the SBR component contained in the negative electrode active material layer is 1.5% to 3% by mass can suppress the reduction of the charge and discharge cycle characteristics.

[0132] Description of Reference Numerals

[0133] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 15 battery case, 16 case body, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 bulging portion, 23 filter, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cap, 28 gasket, 30 graphite particles, 32 inter-particle gaps, 34 internal gaps, 36 external gaps.

Claims

1. A non-aqueous electrolyte secondary battery comprising a negative electrode having a negative electrode active material layer, The negative electrode active material layer includes: a negative electrode active material containing graphite particles and at least one SBR component selected from styrene-butadiene copolymer rubber and modified products thereof. The carbon material in the negative electrode active material layer contains only the graphite particles. The internal porosity of the graphite particles is 1% to 5%, the interparticle porosity of the negative electrode active material layer is 10% to 20%, and the content of the SBR component is 1.5% to 3% by mass relative to the mass of the negative electrode active material.

2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The saturated tap density of the negative electrode active material is 0.8 g / cm 3 ~1.2g / cm 3 .

Citation Information

Patent Citations

  • Secondary battery with non-aqueous solvent

    JP1992342966A

  • Nonaqueous electrolyte secondary battery

    JP1997007597A

  • Electrochemical battery fined carbon

    JP1997320600A

  • Carbonaceous material for electrode for non-aqueous solvent type secondary battery and manufacture thereof, as well as non-aqueous solvent type secondary battery

    JP1998021919A

  • Graphite grain, its production, graphite paste using graphite grain, negative electrode for lithium secondary battery, its production and lithium secondary battery

    JP1998236809A